(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The lack of efficiency and effectiveness of farmers in producing and selling agricultural products due to the impact of Covid-19, by using information technology these problems can be reduced. One product of the rapid development of information technology is E-commerce. In this modern world, e-commerce (Electronic Commerce) has had a major influence on the growth of the social and economic order of society. The aim of this program is that the people of Kampung Padang Serai Bengkulu can find what they need and need in managing their agricultural land by using information and communication technology that they understand from program socialization.